Children's use of objects in an early years playground. Issue 1 (2nd January 2017) - Bateman, Amanda; Church, Amelia
ABSTRACT: Early childhood research has investigated children's use of objects largely focusing on cognitive and motor development. Yet members of a particular culture, such as young children's peer groups, use objects that have cultural relevance as conversational items, as a means to interacting with other members of the group. This article illustrates the role of objects in children's everyday lives by demonstrating how children orient to objects as a way of approaching an existing group. The findings are taken from a study using conversation analysis (CA) to explore playground interactions between four-year-old children in a Welsh primary school. The analysis reveals that children systematically use objects as access tools to initiate interactions with each other, thereby using immediately available resources – and exploiting the sequential rules of talk – to co-construct the social organisation of the playground.